Analysis of the Healing Architecture Approach to the Gelora Bung Karno Sports Complex, Jakarta - Marsyafita Shabrina; Citra Persada (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
Jakarta faces significant urban challenges, including congestion, pollution, and a lack of green spaces, which negatively impact public health. The Gelora Bung Karno (G.B.K.) Sports Complex holds substantial potential to enhance physical and mental well-being by integrating healing architecture principles. This study identifies and analyses the architectural elements at G.B.K. that contribute to a healthier environment, such as natural lighting, green spaces, and environmentally friendly materials. The research initially employed a qualitative approach, collecting data through field observations and literature reviews. However, this updated approach incorporates quantitative methods by introducing measurable indicators for the effectiveness of healing architecture at G.B.K., using surveys and statistical analysis to assess user satisfaction and well-being. The findings suggest that integrating healing architecture in G.B.K. significantly enhances environmental quality and public health, making it a model for urban spaces in Jakarta. The discussion highlights the importance of natural elements, spatial design, and user-centred facilities in creating environments conducive to both mental and physical health. The study concludes that while G.B.K. effectively embodies the principles of healing architecture, further improvements in artificial lighting, thermal comfort, and user-specific spaces could elevate its role as a therapeutic urban environment. Recommendations include expanding green spaces, optimizing lighting systems, and enhancing public participation in developing G.B.K. to ensure its long-term sustainability as a healing space.